تحولات الدولة الريعية وانعكاساتها على البنية الاجتماعية-السياسية : دولة الإمارات العربية المتحدة نموذجا - ميسري، إحسان عبد الله محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research attempts to clarify the impact of the transformations of the rentier state on the socio-political structure of the United Arab Emirates (UAE) during the period 2006-2016. The main objective of this dissertation is to ascertain the social and political effects of the rentier model of governance and the major indicators of the regression of that model of governance within the context of the UAE. An equally important objective of the study is to delineate the parameters of the old social contract of the UAE, and to shed light on the characteristics of the new social contract which posits that citizens of the UAE have consented to surrender some of their freedoms and submit to the authority of their rulers in exchange for protection of their remaining rights. The basic research problem revolves around the question of how the UAE with the regression of the rentier mentality to effect a restructuring of the current social contract in such a way that would ensure public participation without endangering political stability and social security of the Emirati society. The major findings of this research indicate that in its nascent years as a state, the UAE was almost totally reliant on one commodity, oil. However, in the last few years, the state has witnessed a series of socio-political and economic transformations that paved the way of transition from the rentier economy to successful efforts at economic diversification. These transformations have enormously reduced the pattern of GDP based on oil and gas output. This has been achieved by following long-range strategies that would ensure a smoother transition to the post-rentier era. This transition is painful and slow and requires more time after long years of reliance on one commodity. It seems that the ruling elites have deliberately chosen an incremental/ gradual approach to restructure the rentier basis of the country's economy. The social and political structures of the state have also witnessed a relatively dynamic transformation as a result of the endorsement of the new social contract. This new formula is expected to ensure the welfare state status for the citizens. However, it has to be noted that the new status is completely different from the one that had characterized the old regime that emerged in 1971. Based on this new vision, the ruling elites are affecting a paradigm shift that would transcend the rentier stage and that would serve as a roadmap for the new social contract. A corollary of this transformation is a more sustained effort to spend more on health care, education and infrastructure. The country is today less reliant on oil and gas than in previous years. The political elites are also aware of the need for opening up of the political system for more empowerment of the citizens but at the same time to ensure the stability of the political system. The policies of this new social contract have covered the administrative, political, religious, social and cultural domains. This multiplicity requires the researcher to utilize different research designs and approaches that cut across different disciplines, including political science, economics and sociology. In addition, the research is using the historical approach to chronologically follow the evolution of the UAE and the impact of the oil discovery on its development. Simultaneously, the research avails itself of the analytical approach to explore and explain the nature of the transformations that the country has witnessed. The information/data for this research are derived from both primary and secondary sources. The former depends mainly on official statistical and documentary sources, interviews with ministers and experts, the latter derives mainly from library materials like books, articles and online materials.